Germline and Somatic mutations in postmenopausal breast cancer patients (Clinics, 2021)
OBJECTIVES: In breast cancer (BC) patients, the frequency of germline BRCA mutations (gBRCA) may vary according to the ethnic background, age, and family history of cancer. Phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA) is the second most common somatic mutated gene in BC; however, the association of mutations in both genes with cancer has not been thoroughly investigated. Thus, our aims were to investigate gBRCA mutation frequency in a cohort of postmenopausal Brazilian BC patients and the association of gBRCA1/BRCA2 and PIK3CA somatic mutations.METHODS: Forty-nine postmenopausal (>55 years) and forty-one young (≤35 years) BC patients were included in this study. The postmenopausal group included patients who reported a positive family history of cancer. For these patients, gBRCA1/BRCA2 were sequenced using next-generation sequencing (NGS) or Sanger sequencing. Data for gBRCA in young patients were already available from a previous study. DNA from formalin-fixed, paraffin-embedded (FFPE) tumors was obtained from 27 postmenopausal and 41 young patients for analyzing exons 9 and 20 of PIK3CA. The association between gBRCA1/BRCA2 and somatic mutations in PIK3CA was investigated.RESULTS: The overall frequency of gBRCA1/BRCA2 among the 49 postmenopausal patients was 10.2%. The frequencies of somatic mutations in PIK3CA in the postmenopausal and young patients were 37% and 17%, respectively (ns). The most common PIK3CA mutation was found to be E454A. Nonsense and frameshift mutations, which may counteract the oncogenic potential of PIK3CA were also detected. Regardless of age, 25% of BRCA1/BRCA2 mutation carriers and non-carriers , each, had PIK3CA somatic mutations.CONCLUSIONS: Data obtained indicate that BRCA1/BRCA2 gene testing may be considered for postmenopausal patients with BC who have a family history of cancer. Although some of them are not considered pathogenic, somatic variants of PIK3CA are frequently observed in BC patients, especially in postmenopausal patients.